Changes of Narrative: Osvald Sirén’s Photographic Modeling of Modern Research on Chinese Garden - Jiuwen GU; Yuanfeng SHI; Shan JIA (Fengjing Yuanlin)
ObjectivePhotography, as an innovative method of recording Chinese gardens in the late nineteenth and early twentieth centuries, has a significant impact on the research on gardens both then and in later generations. In spite of this, garden research and photographic research do not overlap much as they are two parallel disciplines. The purpose of this research is to draw comparisons between photographic representations of space and garden research texts. As an emerging image material and a way to understand and review gardens, photography has driven a shift in gardening research, with the underlying mechanisms being investigated in this research. In addition, the research also explores the interaction between photography’s technical characteristics and gardens’ spatial characteristics.MethodsThis research adopts the case study of Osvald Sirén’s photographic images of Chinese gardens. The first research path takes photography techniques and photographic images as the starting point, and analyzes the tone threshold of photographic images to figure out the technical points of Osvald Sirén’s photography, with a focus on the quality of shadow, as well as the characteristics of the images of gardens that are reproduced under the scenarios in which these photography techniques are applied. Furthermore, this research examines how people’s perceptions of garden space have changed as a result of these characteristics. Another path is based on Osvald Sirén’s research experience, which aims to conduct a comparative study between photographic images and written documents regarding Osvald Sirén’s writings and research texts on Chinese gardens, so as to explore the reverse shaping of garden memories and garden understandings through image technology. This research is based on the intersection between the history of gardens and the history of photography, and provides an in-depth analysis of the interactions between garden space and photographic technique to explore their internal, non-obvious connections.ResultsThe results show that Osvald Sirén used a large-format camera, a medium-focal-length lens, and technical concepts similar to those of the zone system to increase the density of image shadow, deepen the details, and compress space during photographing. His early research on art history profoundly influences his approach to expressing photography and his perspective on interpreting gardens. The gardens photographed by Osvald Sirén often depict spatial scenes of significant depth. However, the close-up, middle and distant views of images can all be clearly presented, and even the details of the patterns and architectural decorations in the distant view are also very clear. The pursuit of shadow and texture in his photography dilutes the common obsession with space in garden photography. Photographs give an objective and accurate perspective to garden recording, giving birth to a more convincing and neutral approach. Osvald Sirén’s photographs are obviously not satisfied with this. In his images, sensitivity to art mingles with the other side of the extreme pursuit of photography, and gardening expresses the art of living. The expressiveness of Osvald Sirén’s individual works attempts to take into account all such elements as the complexity of gardens, the wandering line of sight brought about by scatter perspectives, the flow of light and the emphasis on the artistic conception of rocks. The localized images taken from different perspectives construct a distinct narrative language of gardens, an alternative spatial narrative language to the traditional garden narrative, accompanied by the emergence of an emerging research branch of garden space reading logic — a school of garden research based on modern iconography.ConclusionPhotographic interventions in garden space research were constrained by many technical conditions which posed substantial challenges to early photography. Osvald Sirén clearly solved these technical problems skilfully, and this is what distinguishes his works as valuable works of art from common garden photography. He applied a concept very similar to the area exposure method, generating images with personal characteristics. At the same time, these images of gardens with great detail content have formed a strong set of garden narratives, which in turn influence the perspective of garden research — a spatially compressed perspective with multiple details superimposed on each other, and a perspective that transforms spatial protagonists and garden narratives, which has begun to subconsciously influence the direction of garden research. The combination of this influence and western spatial research has formed a very common paradigm for garden research. From another perspective, photography interventions in garden space research are constrained by a plethora of technological conditions. This process of overcoming photographic practice constraints is also the driving force behind photographic equipment iteration. Photographers’ strong artistic aspirations under limited technical conditions have given garden photography, as a sub-category of photography, an exceptional artistic character. As a microcosm of the application of photography by modern overseas sinologists in their research on China, Osvald Sirén’s photographic practice provides an original and accessible perspective for the modernization of modern research.